2018
DOI: 10.1136/jim-2017-000556
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Profiles of Urinary Micrornas May Explain Podocyte Injury and Proximal Tubule Dysfunction in Normoalbuminuric Patients with Type 2 Diabetes Mellitus

Abstract: MicroRNAs (miRNAs) are short non-coding RNA species that are important post-transcriptional regulators of gene expression. The aim of the study was to establish a potential explanation of podocyte damage and proximal tubule (PT) dysfunction induced by deregulated miRNAs expression in the course of type 2 diabetes mellitus (DM). A total of 68 patients with type 2 DM and 11 healthy subjects were enrolled in a cross-sectional study and assessed concerning urinary albumin:creatinine ratio (UACR), urinary -acetyl-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
1
13
0
1
Order By: Relevance
“…Ye et al [36] and Hara et al [37] showed that positive urinary PCX could be used as a noninvasive marker of earlystage DN. The urinary and plasma levels of some miRNAs were associated with the urinary levels of PCX and were also associated with proximal tubule injury [38,39]. Metformin has been shown to restore PCX expression in diabetic rats [40], but a study suggested that dipeptidyl peptidase-4 (DDP-4) inhibitors and α-glucosidase inhibitors did not change the urinary levels of PCX [41].…”
Section: Renal Podocalyxin Expressionmentioning
confidence: 99%
“…Ye et al [36] and Hara et al [37] showed that positive urinary PCX could be used as a noninvasive marker of earlystage DN. The urinary and plasma levels of some miRNAs were associated with the urinary levels of PCX and were also associated with proximal tubule injury [38,39]. Metformin has been shown to restore PCX expression in diabetic rats [40], but a study suggested that dipeptidyl peptidase-4 (DDP-4) inhibitors and α-glucosidase inhibitors did not change the urinary levels of PCX [41].…”
Section: Renal Podocalyxin Expressionmentioning
confidence: 99%
“…The ocular surface is very vulnerable to oxidative stress and its properties change as a result of stress. Microand macro vessels are affected by hyperglycaemia, endothelial cells become dysfunctional and play a critical role in severe changes along the vascular wall [22].…”
Section: Resultsmentioning
confidence: 99%
“…The serum and urinary specimens of patients and controls utilized for the assessment of UACR, cystatin C, KIM-1, NAG, synaptopodin, and podocalyxin were frozen at -80 °C and thawed before assay. Urinary biomarkers were evaluated in the same first morning urine sample 8 , 19 , 20 . The biomarkers of podocyte injury (synaptopodin, podocalyxin) and of PT dysfunction (KIM-1, NAG), were reported as per urinary creatinine ratio.…”
Section: Methodsmentioning
confidence: 99%
“…MiRNAs with negative or protective roles, either at renal level or both at renal and vascular level, have been thoroughly studied in the course of DKD 4 , 5 , 6 , 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation